AstraZeneca's covid-19 (mis)adventure and the future of vaccine equity. (11th November 2022) - Fortner, Robert
Abstract : The pandemic brought vaccine equity to the forefront of public health consciousness like never before—yet the world seems no closer to it. Robert Fortner asks what, if anything, has been learnt